1993
DOI: 10.1056/nejm199306243282504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation with Very-Long-Chain n-3 Fatty Acids in Patients with Psoriasis

Abstract: Dietary supplementation with very-long-chain n-3 fatty acids was no better than corn-oil supplementation in treating psoriasis. Clinical improvement was not correlated with an increase in the concentration of n-3 fatty acids in serum phospholipids among the patients in the fish-oil group, whereas there was a significant correlation between clinical improvement and an increase in eicosapentaenoic acid and total n-3 fatty acids in the corn-oil group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 30 publications
1
84
1
5
Order By: Relevance
“…Soyland et al [19] conducted a 4-month, double-blind, randomized, placebo-controlled, multicenter trial among 145 patients with moderate-to-severe plaque psoriasis. The patients were randomly assigned to either the fish-oil group, in which each patient received six capsules daily (each capsule had 1 g of omega-3 fatty acids(51% EPA, 32% DHA) or to the control group in which each patient received six capsules of corn oil daily (each capsule containing 1 g of omega-6 fatty acids (26% oleic acid, 56% linoleic acid); the score of the Psoriasis Area and Severity Index (PASI) levels did not change significantly in either group at the end of the trial.…”
Section: Fish Oil and Psoriasismentioning
confidence: 99%
“…Soyland et al [19] conducted a 4-month, double-blind, randomized, placebo-controlled, multicenter trial among 145 patients with moderate-to-severe plaque psoriasis. The patients were randomly assigned to either the fish-oil group, in which each patient received six capsules daily (each capsule had 1 g of omega-3 fatty acids(51% EPA, 32% DHA) or to the control group in which each patient received six capsules of corn oil daily (each capsule containing 1 g of omega-6 fatty acids (26% oleic acid, 56% linoleic acid); the score of the Psoriasis Area and Severity Index (PASI) levels did not change significantly in either group at the end of the trial.…”
Section: Fish Oil and Psoriasismentioning
confidence: 99%
“…LTB4 was found to have significantly decreased in the treatment group (P < 0.03) but not in the control group. The other six studies 5,6,14,15,17,18 reported no significant reduction in scaling, erythema, area involved or thickness. Gupta et al 5 reported the mean time period elapsed before the psoriasis worsened to pre-therapy severity was 4.9 AE 0.5 weeks in the intervention group and 4.5 AE 0.6 weeks in the control group (P = 0.4).…”
Section: Description Of Included Studiesmentioning
confidence: 91%
“…They also reported a significant rise in serum concentration of EPA and fall in the ratio of AA to EPA and n-3 to n-6 PUFA after treatment (P < 0.01). 15 Soyland et al 17 reported a significant decrease in the infiltration and scaling scores (P < 0.01) in the intervention group, but also a significant decrease from baseline in the scores for desquamation (P < 0.05), redness (P < 0.05) and scaling (P < 0.01) in the control group; however, there were no significant differences between the two groups. Interestingly, Soyland's study also found that the concentration of EPA increased 3.6-fold, whereas DHA increased by 39% in serum phospholipids in subjects who received n-3 PUFA.…”
Section: Description Of Included Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…
The n-3 polyunsaturated fatty acids contained in fish oil provide it with anti-inflammatory effects on different inflammatory diseases (1,2) . Several mechanisms can be involved in the influence of the degree of unsaturation of dietary fatty acids on the development of inflammatory diseases (3) .
…”
mentioning
confidence: 99%